2020
DOI: 10.3389/fnbeh.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol Exposure During Adolescence or Adulthood on Locomotor Sensitization and Dopamine Levels in the Reward System

Abstract: Behavioral sensitization is a process of neuroadaptation characterized by a gradual increase in motor behaviors. The major neural substrates involved in the behavioral sensitization lie on the dopaminergic mesocorticolimbic pathway, which is still under development during adolescence. To investigate age-differences in ethanol behavioral sensitization and dopamine levels in distinct brain regions of the reward system, adolescent and adult mice were repeatedly pretreated with saline or ethanol (2.0 g/kg i.p.) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 72 publications
2
16
0
Order By: Relevance
“…Furthermore, nicotine has been shown to increase dopamine release in the NAc in both adults and adolescent rats [ 62 ]. On the other hand, repeated ethanol administration in mice resulted in sensitization only in adults but not adolescents [ 63 ]. These authors also showed that adolescent mice exhibited lower dopamine levels in the PFC and NAc following ethanol exposure than adults [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nicotine has been shown to increase dopamine release in the NAc in both adults and adolescent rats [ 62 ]. On the other hand, repeated ethanol administration in mice resulted in sensitization only in adults but not adolescents [ 63 ]. These authors also showed that adolescent mice exhibited lower dopamine levels in the PFC and NAc following ethanol exposure than adults [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nicotine has been shown to increase dopamine release in NAc in both adults and adolescent rats (Marusich et al 2017). On the other hand, repeated ethanol administration in mice resulted in sensitization only in the adults, but not adolescents (Carrara-Nascimento et al 2020). These authors also showed that adolescent mice exhibited lower dopamine levels in the PFC and NAc following ethanol exposure, compared to adults (Carrara-Nascimento et al 2020).…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, repeated ethanol administration in mice resulted in sensitization only in the adults, but not adolescents (Carrara-Nascimento et al 2020). These authors also showed that adolescent mice exhibited lower dopamine levels in the PFC and NAc following ethanol exposure, compared to adults (Carrara-Nascimento et al 2020). Cumulatively, based on the published data, it could be suggested that a greater CPP response following amphetamine in adult mice, observed in our study, could be related to dynamic changes in ethanolinduced decrease in dopamine release in NAc between adolescent and adult mice or a combination of action of nicotine and alcohol pre-exposure.…”
Section: Discussionmentioning
confidence: 96%
“…Relatively fewer studies, however, have explored ethanol’s impact on dopamine transmission following adolescent exposure. There is some evidence that adolescent ethanol exposure between postnatal days (PDs) 30 and 45 can decrease accumbal dopamine tissue content in male mice when assessed following five days of abstinence [ 24 ]. Interestingly, intermittent ethanol exposure between PDs 30 and 50, followed by 15 days of abstinence, resulted in elevated basal levels of dopamine in the NAc in adult rats [ 25 ].…”
Section: Introductionmentioning
confidence: 99%